Pengaruh Perceived Organizational Support dan Work Environment terhadap Employee Performance melalui Employee Engagement - Risky Atika Husna; Budiono Budiono (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study aims to study the effect of perceived organizational support and work environment on employee performance through employee engagement among bank employees in Surabaya. This study uses a type of causality research that uses quantitative. The sampling technique used is accidental sampling, with the number of respondents as many as 85 people at bank employees in Surabaya. The statistical analysis used in this study is the Structural Equation Model (SEM) with the support of Smart PLS 3.3.3 software. The result shows that the work environment positively and significantly affects employee engagement. Employee engagement has a positive and significant impact on employee performance. The work environment indirectly affects employee performance through employee engagement because engagement among employees can improve their teamwork, which could be high performance. The company must develop its work environment to increase engagement and improve performance.